2015
DOI: 10.18393/ejss.2015.3.185-190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rice husk compost application on soil quality parameters in greenhouse conditions

Abstract: Effects of rice husk compost (RHC) on some soil quality parameters under greenhouse conditions were investigated. Experiment were conducted in a randomized plot design with different application doses of RHC (0, 3, 6 and 9%) into surface soil (0-20 cm) with three replications in a greenhouse of Agricultural Faculty in Ondokuz Mayıs University. RHC application generally improved the soil quality parameters according to the control treatment during the experiment carried out with growing tomato plant in the gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 17 publications
6
37
0
2
Order By: Relevance
“…Candemir and Gülser (2010) reported that tobacco waste application into a clay soil increased soil pH after 16, 23 and 30 months of the application in a field study. However, Demir and Gülser (2015) reported that 3, 6 and 9% applications of rice husk compost into moderately alkaline soil decreased soil pH. …”
Section: Changes In Soil Ph Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Candemir and Gülser (2010) reported that tobacco waste application into a clay soil increased soil pH after 16, 23 and 30 months of the application in a field study. However, Demir and Gülser (2015) reported that 3, 6 and 9% applications of rice husk compost into moderately alkaline soil decreased soil pH. …”
Section: Changes In Soil Ph Valuesmentioning
confidence: 99%
“…According to the control soils, bicarbonate extractable mean P contents of Tepecik, Kurupelit and Çetinkaya soil series significantly increased 57.9, 41.8 and 39.1%, respectively (Table 4). Demir and Gülser (2015) reported that application of 9 % rice husk compost into soil increased available P content from 60 to 120 ppm, significantly. According to the statistical analysis of data given in Table 4, bicarbonate extractable P values were significantly different in soil series at 0.01 level.…”
Section: Bicarbonate Extractable Phosphate Contents Of Soilsmentioning
confidence: 99%
“…Under this circumstances, using of organic manures such as compost, vermicompost, barnyard manures and biofertilizers is ecofriendly, easily avaliable and cost effective. It is reported that organic materials provide nutrient conversion of organic fertilizer and mineral fertilizer combination, protection of soil moisture, increasing of cation exchange capacity, improving soil physical and biological properties and providing control of erosion [6][7][8][9][10]. Among the organic materials peat often enchances aeration and water retention [11].…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops (CCs) is defined as crops that provides soil protection, seedling protection, and soil improvement between vines in vineyards and trees in orchards between periods of normal crop production, or between periods of normal crop production (SSSA, 2001). Cover crop management systems affect soil quality variables (Demir and Gülser, 2015;Çerçioğlu et al, 2019) and health and thereby orchards growth and productivity. CCs also are precisely grown to prevent loss of nutrients in deep layers through surface runoff and leaching (Kaye and Quemada, 2017).…”
Section: Introductionmentioning
confidence: 99%